1979
DOI: 10.1002/1097-0142(197902)43:2<718::aid-cncr2820430247>3.0.co;2-r
|View full text |Cite
|
Sign up to set email alerts
|

Management of asparaginase induced hemorrhagic pancreatitis complicated by pseudocyst

Abstract: Asparaginase induced hemorrhagic pancreatitis is a rare but serious development occurring in less than 0.5% of patients treated with this drug. Severe pancreatitis with progressive abdominal distention, toxemia, hypotension and respiratory insufficiency occurred in an 18-year-old patient with acute lymphoblastic leukemia following treatment with asparaginase. There was a dramatic response to high flow peritoneal lavage with rapid recovery within 24 hours from a moribund state. The subsequent development of a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
8
1
1

Year Published

1982
1982
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(14 citation statements)
references
References 19 publications
4
8
1
1
Order By: Relevance
“…Previous reports, however, suggest that L-Asp is the more likely source of pancreatitis based on histological examination of the pancreas, the relative infrequency of prednisone-induced pancreatitis, and a negative result after rechallenge with prednisone [3,5,6,8]. In addition, our results showed that the levels of trypsin and elastase-1 during prednisone therapy alone were not signi®cantly higher than those before L-Asp therapy.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Previous reports, however, suggest that L-Asp is the more likely source of pancreatitis based on histological examination of the pancreas, the relative infrequency of prednisone-induced pancreatitis, and a negative result after rechallenge with prednisone [3,5,6,8]. In addition, our results showed that the levels of trypsin and elastase-1 during prednisone therapy alone were not signi®cantly higher than those before L-Asp therapy.…”
Section: Discussionsupporting
confidence: 91%
“…There have been many reports of L-Asp-induced pancreatitis [4,5,10,13], but few studies have examined the relationship between L-Asp therapy and acute pancreatitis by measuring changes in serum levels of pancreatic enzymes [3,4]. Furthermore, there is no study that has evaluated the usefulness of trypsin and elastase-1 measurements in the diagnosis of L-Asp-induced pancreatitis.…”
Section: Discussioncontrasting
confidence: 68%
“…Elevation in serum amylase and lipase are additional manifestation of pancreatitis. Complications that require surgical interventions are exceedingly rare; these include pancreatic pseudocysts [160,[163][164][165][166][167][168]. Some patients develop signs and symptoms of diabetes due to damage in islet cells, and subsequent decrease in synthesis of insulin.…”
Section: Toxicitymentioning
confidence: 99%
“…Although there have been many reports of ASNase-induced pancreatitis, [6,9,[12][13][14][15][16] few studies have examined the relationship between ASNase therapy and acute pancreatitis by measuring changes in serum levels of pancreatic enzymes or plasma levels of amino acids. [15,17,18] As in previous studies, [19,20] in the present study the plasma asparagine levels decreased rapidly after the first ASNase injection.…”
Section: Discussionmentioning
confidence: 99%
“…[23] Previous reports suggest that ASNase is the more likely source of pancreatitis on the basis of histologic examination of the pancreas, the relative infrequency of prednisolone-induced pancreatitis, and a negative result after rechallenge with prednisolone. [14,18,24] In the present study, one of 29 patients (3%) developed ASNase-induced pancreatitis, similar to the morbidity rates in previous reports. [4,6,9,16,25] Since the patient developed severe pancreatitis, ASNase was contraindicated during the rest of her treatment for ALL.…”
Section: Discussionmentioning
confidence: 99%